1-(Piperidin-3-yl)thymine amides as inhibitors of M. tuberculosis thymidylate kinase - Yanlin Jian; Martijn D. P. Risseeuw; Mathy Froeyen; Lijun Song; Davie Cappoen; Paul Cos; Hélène Munier-Lehmann; Serge van Calenbergh (Taylor & Francis Group, 2019)
A series of readily accessible 1-(piperidin-3-yl)thymine amides was designed, synthesised and evaluated as Mycobacterium tuberculosis TMPK (MtbTMPK) inhibitors. In line with the modelling results, most inhibitors showed reasonable MtbTMPK inhibitory activity. Compounds 4b and 4i were slightly more potent than the parent compound 3. Moreover, contrary to the latter, amide analogue 4g was active against the avirulent M. tuberculosis H37Ra strain (MIC50=35 µM). This finding opens avenues for future modifications.